Toward the implications of technology- based education and EFL learners' anxiety for instructions - Chen, Ruohan; Boon, Sim Ng; Paramasivam, Shamala (Tarbiat Modares University, 2023)
Impressive speculation has been made to carry technology to schools and these ventures have for sure brought about a large number of "examples of overcoming adversity". Nonetheless, there is one critical gap in the instructive purposes of technology that should be addressed. Research shows that although most teachers and students tend to use these tools in language teaching skills, they refuse to to do so for fear of using technology tools in the classroom; therefore, to shed light on different aspects of this critical point, the present study reviewed the possible relationship between technology and students' fear and anxiety in the literature. The findings of this study showed that teachers and students who have a high level of computer knowledge are less afraid of technology. The findings also showed that another factor of language learners' reluctance of using technology is their teachers' belief about the effectiveness of these tools. The results of the present study provide suggestions for training language teachers to educational planners about a more efficient process of language teaching due to the new needs in the use of technology in English language teaching. A significant implication, thusly, is that the training and preparation of teachers and instructors ought to turn into a need in creating technology-related proficient turn of events.